Secretory Leukocyte Protease Inhibitor (SLPI) Decreased the Celluler Expression of NF-Kβ and IL-1β on Wound Macrophages of Rattus novergicus Post Tooth Extraction - Agustine Hanafi Putri; Abdur Razaq Komaruzzaman; Putri Noerpuspita; Delfi Fitriyani; Nur Permatasari; Edi Widjajanto (Journal of Tropical Life Science, 2016)
Prevalence of tooth extraction or dental surgery was 48.5% of all dental care in Indonesia. Tooth extraction carries potential health risks and side effects such as pain, swelling, trismus and dysfunction of the oral cavity during recovery. Secretory leukocyte protease inhibitor (SLPI) is one of innate immunity proteins that can inhibit the activation of macrophages. We are expecting the provision of SLPI can decrease excessive inflammatory response in healing after tooth extraction. This study was to investigate the administration of SLPI on cellular expression of NF-Kβ and IL-1β on wound macrophages of Rattus novergicus post tooth extraction. The research design is in vivo experimental study. In total, 20 rats were randomly divided into four groups (each group n=5) and underwent tooth extraction on left incisor teeth of mandible. One of the groups did not receive SLPI administration (control group) and the socket was stitched after tooth extraction. Meanwhile, the remaining three groups (experimental groups) were given SLPI administration after tooth extraction with three different doses (0.1 µM, 0.5 µM and 2.5 µM, respectively). After SLPI administration, the socket of experimental groups was stitched. The effects of SLPI administration were evaluated by counting at the percentage of NF-Kβ translocation and the expression of expression of IL-1 in macrophages cells of the rat socket using immunohistochemistry analysis. The cellular expression of NF-Kβ and IL-1β were significantly decreased (p < 0.05) on groups with SLPI may decrease cellular expression of NF-Kβ and IL-1β on wound macrophages cells of rats post tooth extraction in a dosedependent manner.